Macroalgae as an eco-friendly and successful green technology for the removal of crystal violet from synthetic and real wastewater - Shazia, Bibi (2023)
Crystal violet (CV) is one of the water pollutants that can cause potential harm to living beings and the environment. Different methods are applied for the removal of CV from wastewater, however, a cheap and environmentally friendly way is preferred. In this study, Hormophysa triquetra (HT) and its silver-modified form (AgHT) were used for the removal of CV from synthetic and real wastewater. Both physical and chemical characterizations of HT and AgHT were carried out using scanning electron microscopy – energy dispersive X-ray analysis (SEM-EDX), Transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), zeta potential (ζ-potential), and Brunauer-Emmet-Teller (BET) analysis. Different parameters such as pH, temperature, and concentration were studied for the adsorption process. The optimum pH of the adsorption process was 6 with a maximum adsorption capacity of 181.8 mg/g for HT and 312.5 mg/g for AgHT at 45◦C. The best-fitted adsorption isotherm model was the Langmuir model based on the correlation coefficient (R2) however; the chi-square (χ2) analysis indicated the Freundlich model to be the best-fit model. Moreover, the thermodynamics studies indicated a spontaneous and endothermic reaction with HT and the reverse with AgHT. The main functional groups contributing to the adsorption of CV on the adsorbents involve carboxyl, hydroxyl, carbonyl groups, and aromatic rings. The adsorbent removed more than 98 % of CV from real wastewater with AgHT being more efficient than HT. Desorption studies indicated that desorption agents such as NaOH and HCl reduced the electrostatic interactions between the adsorbate and the adsorbent, thereby regenerating the adsorbent. This study proves the use of naturally abundant and available macroalgae as an eco-friendly and successful green technology for the removal of CV from real wastewater.